Students’ Insights from Interactive Visualizations Arranged Multimodally in Knowledge Visualizations - Bodén, Ulrika Christina; Stenliden, Linnea; Nissen, Jörgen (Educare, 2022)
In this study, a visual analytics application is put into practice in Swedish secondary school social science classrooms. The application offers support to analyse vast amounts of data through interactive data visualizations. Previous studies have demonstrated that the visual interactive interface challenges the traditional practice in school, where students usually demonstrate their knowledge by means of written texts. Thus, this study examines what happens if students work with more malleable, adaptable, or fluid modes when attempting to express their conclusions from work with interactive data visualizations. It aims to detect patterns in how knowledge visualizations are produced and arranged multimodally. Inspired by design-based research, the study conducted two classroom interventions followed by video captures. It employed a socio-material semiotic approach, which enables the study of interactions between both social and material actors. Three patterns emerged when students’ insights were translated into knowledge visualizations – exploring, gathering, and inserting. It became obvious how different actors taking part of such a digital multimodal writing activity affect and change every actor/everyone/everything, which in turn transfers, relocalizes, reformulates, and re-presents the communicated message. Knowing how knowledge visualizations are produced might strengthen students’ visual abilities when transforming insights multimodally.